The Role of Ad Hoc Judges in Resolving Corruption Crime Issues - Christa Lumamuly; Loisa Marga Metekohy; Remon Bakker (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is a qualitative descriptive research that aims to find out how the role of ad hoc corruption judges is in resolving corruption cases. the problem of criminal acts of corruption in class 1 A Ambon district court. This research was carried out at the District Court/Industrial Relations/Tipikor/Fisheries Ambon Class 1 A. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved. The data collection techniques used were observation, interviews and documentation. The results of these interviews can show that ad hoc judges have carried out their duties and responsibilities properly in resolving the problem of criminal acts of corruption. At first they were dissatisfied with the performance of the career judges who handled corruption cases, but the presence of ad hoc judges helped them resolve cases properly.